When private actors contribute to public interests : a law and governance perspective - McCann, Adam (Governance & recht ;, 2014)
This volume of the Netherlands Institute for Law and Governance series is the result of a PhD Roundtable Forum on the theme: 'When Private Actors Contribute to Public Interests, ' held in Amsterdam on April 19, 2012. Traditionally, when thinking of the actors responsible for securing or protecting fundamental interests of society, one thinks of public actors: state authorities, government officials, the judiciary, enforcement officers, and politicians. However, the focus of this book is to reflect on the role private actors play with regard to fundamental interests of society; the degree of int.